2022
DOI: 10.5271/sjweh.4068
|View full text |Cite
|
Sign up to set email alerts
|

The association between the use of shift schedule evaluation tool with ergonomics recommendations and occupational injuries: A 4-year prospective cohort study among healthcare workers

Abstract: Previous studies have found that fatigue and impaired sleep quality are associated with occupational injuries, and working hour characteristics and recovery are associated with fatigue and occupational injuries. The current study showed that the use of the shift schedule evaluation tool with ergonomics recommendations was associated with reduced risk of some occupational injuries. The association was mediated through longer recovery periods. Integrating ergonomics recommendations for shift scheduling closely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To support ward managers in creating rosters that are safer for nurses, modern rostering technology could be used to develop ergonomic rotas while also balancing ward coverage, staffing numbers and patient demand. Previous research has demonstrated benefits for health care workers when embedding ergonomic shift work recommendations in rostering software, particularly in terms of reducing adverse working patterns, sleep difficulties and occupational injury (Härmä et al., 2022; Karhula et al., 2021; Shiri & Härmä, 2023), but outcomes related to work‐life balance are less understood. Moreover, nurses may still prefer to work more difficult shift patterns when given the choice (Karhula et al., 2018, 2020), but in these cases, risk could still be mitigated thereafter (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support ward managers in creating rosters that are safer for nurses, modern rostering technology could be used to develop ergonomic rotas while also balancing ward coverage, staffing numbers and patient demand. Previous research has demonstrated benefits for health care workers when embedding ergonomic shift work recommendations in rostering software, particularly in terms of reducing adverse working patterns, sleep difficulties and occupational injury (Härmä et al., 2022; Karhula et al., 2021; Shiri & Härmä, 2023), but outcomes related to work‐life balance are less understood. Moreover, nurses may still prefer to work more difficult shift patterns when given the choice (Karhula et al., 2018, 2020), but in these cases, risk could still be mitigated thereafter (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…injury(Härmä et al, 2022;Karhula et al, 2021;Shiri & Härmä, 2023), but outcomes related to work-life balance are less understood.Moreover, nurses may still prefer to work more difficult shift patterns when given the choice(Karhula et al, 2018(Karhula et al, , 2020, but in these cases, risk could still be mitigated thereafter (e.g. if a nurse prefers to work long shifts only, limit the number of long shifts that are worked in a row).…”
mentioning
confidence: 99%
“…Other recent methodological developments in working hours and health research include experimental stepped-wedge pseudo-randomized trials and the use of the observational propensity score method, where data from large cohorts are clustered or matched in a way that mimics randomization ( 26 , 38 , 39 ). Some recent studies have employed case–crossover designs, which are essentially within-participant variations of case–control studies.…”
Section: The Development Of Epidemiological Methodsmentioning
confidence: 99%
“…One of the consequences of the sleep restriction, fatigue and sleepiness that are associated with night and shift work is the increased risk of occupational injuries. Several studies published in this Journal have observed increased risk of injuries during night work ( 22 26 ) and on work days following night shifts ( 27 ). Similarly, several studies have found elevated risk of occupational injuries on evening shifts ( 22 , 25 , 27 ), suggesting that other work shift-related differences, like higher individual work load in addition to sleep restriction, may contribute to the increased injury risk.…”
Section: Sleep Fatigue and Injuriesmentioning
confidence: 99%
See 1 more Smart Citation